2012
DOI: 10.1038/nn.3132
|View full text |Cite
|
Sign up to set email alerts
|

State and location dependence of action potential metabolic cost in cortical pyramidal neurons

Abstract: Action potential generation and conduction requires large quantities of energy to restore Na(+) and K(+) ion gradients. We investigated the subcellular location and voltage dependence of this metabolic cost in rat neocortical pyramidal neurons. Using Na(+)/K(+) charge overlap as a measure of action potential energy efficiency, we found that action potential initiation in the axon initial segment (AIS) and forward propagation into the axon were energetically inefficient, depending on the resting membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
225
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(239 citation statements)
references
References 58 publications
14
225
0
Order By: Relevance
“…This is not, however, their sole function; action potentials are also important for preventing noise accumulation in successive layers of information processing in neural circuits. The energy consumption of a single action potential within a single neuron would be challenging to measure directly, so typically it is estimated by converting the electrical signals into the total amount of work the 3Na + /2K + pump must do to restore ion gradients (Box 1) [9,[25][26][27][28][29][30][31][32][33][34][35][36]. Estimates of action potential energy consumption are, consequently, dependent upon accurate measurement of biophysical parameters including channel kinetics, conductance magnitudes and membrane capacitances.…”
Section: Action Potential Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not, however, their sole function; action potentials are also important for preventing noise accumulation in successive layers of information processing in neural circuits. The energy consumption of a single action potential within a single neuron would be challenging to measure directly, so typically it is estimated by converting the electrical signals into the total amount of work the 3Na + /2K + pump must do to restore ion gradients (Box 1) [9,[25][26][27][28][29][30][31][32][33][34][35][36]. Estimates of action potential energy consumption are, consequently, dependent upon accurate measurement of biophysical parameters including channel kinetics, conductance magnitudes and membrane capacitances.…”
Section: Action Potential Energy Consumptionmentioning
confidence: 99%
“…It was assumed that the energy consumption of this action was broadly representative of other action potentials [9]; however, this was dispelled by combining experimental measurements and computational modelling of a range of action potentials primarily from mammalian neurons [26][27][28][29]. This demonstrated that the squid giant axon action potential was profligate in its energy consumption compared to most other action potentials, and revealed a hitherto unappreciated heterogeneity in the biophysics of the currents generating action potentials and their consequences for the energy consumption of the action potential [25][26][27][28][29][30][31][32][33][34][35][36]. The major cause of differences in energy consumption was identified as the overlap between the inward and outward currents during the action potential [26,28,34,35]: A large overlap inflates energy consumption whereas complete separation of the currents reduces energy consumption close to the minimum possible.…”
Section: Heterogeneity In Action Potential Costsmentioning
confidence: 99%
“…To mimic this situation of suprathreshold neuronal activity, Na ϩ recordings were performed in dendrites following a transient large increase in [Na ϩ ] i . The energy cost for turn-over of Na,K-ATPase is estimated to be ϳ50% of total brain energy consumption (16) and because sev-eral lines of evidence suggest that the majority of this Na ϩ current dependent energy is expended postsynaptically rather than presynaptically (17), the Na ϩ imaging studies were performed on dendrites.…”
mentioning
confidence: 99%
“…From the total Na + flux during an action potential in both somatic and axonic compartments, and using standard methods (e.g. Alle et al, 2009;Sengupta et al, 2010), we calculate the cost of a single action potential in a P neuron to be about 10 9 ATP molecules (Fig.4C); this is similar to, but on the high end of the range of, previous estimates for other neurons (Attwell and Laughlin, 2001;Lennie, 2003;Hallermann et al, 2012). Note that such estimates depend strongly on the relative gating kinetics of the Na + and K + channels and can vary significantly between neurons (Sengupta et al, 2010).…”
Section: Electromotor Network: Pacemaker Nucleusmentioning
confidence: 67%
“…Alle et al, 2009;Sengupta et al, 2010). Such estimates suggest that each action potential consumes between 10 7 and 10 9 ATP molecules depending on neuron type (Attwell and Laughlin, 2001;Lennie, 2003;Sengupta et al, 2010;Hallermann et al, 2012;. Thus, an action potential in just a single neuron can consume an order of magnitude more energy than the minimal amount required to assemble the electric field, suggesting that the actual cost of EOD generation must be several orders of magnitude higher than this theoretical lower bound.…”
Section: Action Potential Energeticsmentioning
confidence: 99%